Indonesia dan Fundamentalisme Keagamaan - Sri Suwartiningsih (Yayasan Bina Darma, 2015)
Religion is a human life guidance. Religion is not God's creation. Religion is a human creation to be able to steer and control his life. Life associated with the Creator. So that religion is a tool in relations human relationship with God, which is a vertical relationship. At the moment in the life of religious fundamentalism used to relate to God, religion becomes a human privatization. But when religion is imposed uniformity fundamental in the understanding, the result can lead to differing views on religion that leads interference to peace among peoples, such as defamation, inter-religious conflicts, homelessness particular religion, terrorism, etc. On this context, fundamentalism and religious diversity is important to be studied and examined the truth. Religious fundamentalism creates open communication space between religious communities in religious equality. In contrast, fundamentalism closed and give communication barriers between religious communities because each considers the most true religion and other religions do not. Indonesia as a pluralistic country requires openness in diversity.Keywords: Religion, Fundamentalism, Peace